Age related changes in NAD+ metabolism oxidative stress and Sirt1 activity in wistar rats. - Nady Braidy; Gilles J Guillemin; Hussein Mansour; Tailoi Chan-Ling; Anne Poljak; Ross Grant (PLoS ONE, 2011)
The cofactor nicotinamide adenine dinucleotide (NAD+) has emerged as a key regulator of metabolism, stress resistance and longevity. Apart from its role as an important redox carrier, NAD+ also serves as the sole substrate for NAD-dependent enzymes, including poly(ADP-ribose) polymerase (PARP), an important DNA nick sensor, and NAD-dependent histone deacetylases, Sirtuins which play an important role in a wide variety of processes, including senescence, apoptosis, differentiation, and aging. We examined the effect of aging on intracellular NAD+ metabolism in the whole heart, lung, liver and kidney of female wistar rats. Our results are the first to show a significant decline in intracellular NAD+ levels and NAD:NADH ratio in all organs by middle age (i.e.12 months) compared to young (i.e. 3 month old) rats. These changes in [NAD(H)] occurred in parallel with an increase in lipid peroxidation and protein carbonyls (o- and m- tyrosine) formation and decline in total antioxidant capacity in these organs. An age dependent increase in DNA damage (phosphorylated H2AX) was also observed in these same organs. Decreased Sirt1 activity and increased acetylated p53 were observed in organ tissues in parallel with the drop in NAD+ and moderate over-expression of Sirt1 protein. Reduced mitochondrial activity of complex I-IV was also observed in aging animals, impacting both redox status and ATP production. The strong positive correlation observed between DNA damage associated NAD+ depletion and Sirt1 activity suggests that adequate NAD+ concentrations may be an important longevity assurance factor.